ANALYSIS OF NATIONAL ACTIVITY FOR EXECUTING THE JOINT CONVENTION ON THE SAFETY OF RADIOACTIVE WASTE MANAGEMENT - A. I. Sobolev; I. V. Syreyshchikov (Тонкие химические технологии, 2016)
Analysis of the results of the activity of the State Atomic Energy Corporation "Rosatom" and the Federal Service for Ecological, Technological and Nuclear Supervision for preparing the Russian Federation reports at meetings of the contracting parties to fulfil the obligations arising from the Joint Convention on the Safety of Spent Fuel Management and on the Safety of Radioactive Waste Management was performed.The main content of the report refers to the fourth national report of the Russian Federation submitted to the IAEA in May 2015. The main results of the activity for the formation of a unified state system for RW management were considered. Analysis of the questions of the Member States of the Joint Convention to the content of the national report was performed. A review of the activities of the FSUE "RosRAO" in terms of solving the basic problems for the safe management of radioactive waste was presented.